2022
DOI: 10.3390/foods11244067
|View full text |Cite
|
Sign up to set email alerts
|

Modified Highland Barley Regulates Lipid Metabolism and Liver Injury in High Fat and Cholesterol Diet ICR Mice

Abstract: Highland barley (Hordeum vulgare L. HB) has been demonstrated to have a series of dietotherapy values, including being low fat, low sugar, high fiber, and especially high in β-glucan. Long-term consumption could reduce the incidence of chronic diseases and metabolic syndromes. In this study, the regulating effect of modified highland barley (MHB) products, namely microwave fluidized HB, extruded and puffed HB, and ultrafine pulverized HB on lipid metabolism and liver injury in mice fed a high fat and cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Te above active ingredients have been found to have lipid-lowering, antioxidant, and other efects in recent years [11][12][13]. In addition, after microwaving, baking, and heat fuidization, treated highland barley dietary fber displayed a higher antioxidant activity, β-glucan extractability, and improved liver injury of obese mice [14]. Te above research indicates that the dietary fber in highland barley is a potential cash crop.…”
Section: Introductionmentioning
confidence: 90%
“…Te above active ingredients have been found to have lipid-lowering, antioxidant, and other efects in recent years [11][12][13]. In addition, after microwaving, baking, and heat fuidization, treated highland barley dietary fber displayed a higher antioxidant activity, β-glucan extractability, and improved liver injury of obese mice [14]. Te above research indicates that the dietary fber in highland barley is a potential cash crop.…”
Section: Introductionmentioning
confidence: 90%
“…We then carefully examined each article to ensure that they met our criteria, including full access to the article, a control and experiment group, complete data, and lipid profile parameters. As a result, we identified seven articles that met our requirements and provided us with 11 studies code [5,6,12,13,14,15,16] for analysis using CMA software. The process of data review in this research is shown in Figure 1.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Their mutations (i.e., Niemann–Pick type C disease) lead to massive lysosomal accumulation of cholesterol and sphingolipids (Wanikawa et al., 2020 ). Consequently, HFD enrichment with 1% cholesterol is enough to enhance lipid storage and inflammation in liver of HFD obese mice compared with animals fed with a chow diet (Chang et al., 2021 ; Zhou & Wu, 2022 ). Indeed, HFD impair lysosomal function and autophagic flux (Yamamoto et al., 2017 ).…”
Section: How High‐fat Diets Affect Extracellular Vesicle Lipid Compos...mentioning
confidence: 99%